Modeling of Terahertz Radiation Generation By Femtosecond Laser Pulse of FEW Cycles - G. D. Hovhannisyan; A. H. Vardanyan; A. V. Sahakyan
In this paper, we study the spectrum and time profile of terahertz radiation that generated during the propagation of an extraordinary linearly polarized laser pulse of a few optical cycles in the direction normal to the optical axis of a nonlinear uniaxial crystal of 3m symmetry group. We solve Maxwell’s equations describing the propagation of the laser pulse using the FDTD method. As an example, we calculate the spectrum and time profile of terahertz radiation for laser pump pulse with duration 10fs at 850nm wavelength. As an example, we apply our model to study the propagation of a femtosecond laser pulse in a LiNbO3 crystal of 390um thickness.
Keywords: Physics; Optics